SISTEMA INTELIGENTE PARA EL TRATAMIENTO DE LA INFORMACIÓN Y EL CONOCIMIENTO - Estrada Sentí, Vivian (2011)
Case Based Reasoning is a very useful methodology to address problems where the solutions given to cases resolved are used to solve other similar nature. This paper presents an intelligent computer system capable of creating and analyzing structured knowledge bases and build an expert who offers solutions to decision making. This tool (software) has been developed in Java. Has been applied for teaching purposes and to assess the degree of introduction of information management and economic knowledge in universities. The application of this tool allows the systematic evaluation of this activity is to support decision making.